Role of Airway Recruitment and Derecruitment in Lung Injury - Ghadiali, S. N. (2011)
The mechanical forces generated during the ventilation of patients with acute lung injury causes significant lung damage and inflammation. Low-volume ventilation protocols are commonly used to prevent stretch-related injury that occurs at high lung volumes. However, the cyclic closure and reopening of pulmonary airways at low lung volumes, i.e., derecruitment and recruitment, also causes significant lung damage and inflammation. In this review, we provide an overview of how biomedical engineering techniques are being used to elucidate the complex physiological and biomechanical mechanisms responsible for cellular injury during recruitment/derecruitment. We focus on the development of multiscale, multiphysics computational models of cell deformation and injury during airway reopening. These models, and the corresponding in vitro experiments, have been used to both elucidate the basic mechanisms responsible for recruitment/derecruitment injury and to develop alternative therapies that make the epithelium more resistant to injury. For example, models and experiments indicate that fluidization of the cytoskeleton is cytoprotective and that changes in cytoskeletal structure and cell mechanics can be used to mitigate the mechanotransduction of oscillatory pressure into inflammatory signaling. The continued application of biomedical engineering techniques to the problem of recruitment/derecruitment injury may therefore lead to novel and more effective therapies.